The synovitis of "non-inflammatory" orthopaedic arthropathies: a quantitative histological and immunohistochemical analysis. Issue 8 (18th January 2008) - Pessler, F; Dai, L; Diaz-Torne, C; Gomez-Vaquero, C; Paessler, M E; Zheng, D-H; Einhorn, E; Range, U; Scanzello, C; Schumacher, H R
Abstract : Objective: To quantify inflammatory changes in synovial membranes from orthopaedic "non-inflammatory" arthropathies (Orth. A). Methods: Synovial membranes from patients with femur fracture, avascular necrosis of the femur, plica syndrome, and meniscus and/or ligament injury (n = 23); rheumatoid arthritis (n = 28); osteoarthritis (OA; n = 25); and from normal controls (n = 10) were assessed by light microscopy, a histological synovitis score, immunostaining for CD3, CD20, CD38, CD68, Ki-67 and von Willebrand factor, and with an immunohistochemical inflammation score. Results: Orth. A histology varied between normal and markedly inflamed. Predominant abnormalities were mild lining hyperplasia, scattered inflammatory cells and small perivascular infiltrates. The synovitis score classified Orth. A as "mild synovitis". Inflammatory cells occurred frequently: CD68+ cells in 100% of Orth. A specimens; CD3+, 91%; CD38+, 70%; and CD20+, 39%. Orth. A had 36% greater lining thickness (p = 0.04), 40% higher vascular density (p = 0.009) and 51.3-fold higher CD38+ cell density (p = 0.02) than normal controls; and 60% fewer subintimal Ki-67+ cells (p = 0.003), 42% fewer CD68+ lining cells (p<0.01) and 40% fewer subintimal CD68+ cells (p<0.01) than OA. The immunohistochemical inflammation score was 2.2-fold higher in Orth. A than in controls (p = 0.048) and similar to OA, with three Orth. A specimens showing marked inflammation. Conclusions: Synovial membranes from "non-inflammatory" arthropathies featured neovascularisation and inflammation intermediate between normal and OA synovium. These results expand previous findings that mechanical joint injury may lead to a mild-to-moderate synovitis.